2021
DOI: 10.1111/gwat.13099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rainwater Harvesting on Hydrological Processes in a Fragile Watershed of South Asia

Abstract: Agricultural water management (AWM) interventions play an important role in ensuring sustainable food production and mitigating climate risks. This study was carried out in a watershed located in a low rainfall (400-600 mm) region of western India. The Soil and Water Assessment Tool model was calibrated using surface runoff, soil loss, and reservoir storage levels, between the year 2000 and 2006. The investigation indicated that the various AWM interventions increased groundwater recharge from 30 mm/year to 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Agricultural productivity in these watersheds before the project interventions ranged between 0.5 and 2.0 ton/ha. Nearly 30–40% of agricultural land remained fallow largely due to water scarcity 18 , 19 . More than 90% of the farmers in these watersheds owned less than 2.0 ha, were poor and endured malnutrition 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Agricultural productivity in these watersheds before the project interventions ranged between 0.5 and 2.0 ton/ha. Nearly 30–40% of agricultural land remained fallow largely due to water scarcity 18 , 19 . More than 90% of the farmers in these watersheds owned less than 2.0 ha, were poor and endured malnutrition 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 30–40% of agricultural land remained fallow largely due to water scarcity 18 , 19 . More than 90% of the farmers in these watersheds owned less than 2.0 ha, were poor and endured malnutrition 18 , 19 . Given these conditions, the watersheds were developed as sites of learning by implementing a range of in-situ conservation and ex-situ rainwater harvesting interventions at landscape and farm scales (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have reported that check dams and various rainwater storage structures have harvested 5-10 times the total storage capacity developed in the degraded landscapes of central and western India, with rainfall ranging from 600 to 900 mm (Singh et al, 2014;Garg et al, 2021). AWM interventions enhanced groundwater recharge (by 30-50%), crop productivity (by 50-200%), crop intensification (by 30-50%) and controlled soil erosion and land degradation (by 70-90%) compared to the non-intervention stage (Garg et al, 2011(Garg et al, , 2012aSingh et al, 2014;Garg et al, 2020a;Garg et al, 2021). Garg et al (2011) modelled the impact of various AWM interventions on hydrological processes in the Osman Sagar catchment (736 km 2 ) of the Musi basin in the semi-arid tropics of southern India.…”
Section: Uncertainties In the Modelmentioning
confidence: 99%
“…While the drylands are also beset with poverty and malnutrition largely due to fragmented land holdings, poor production and frequent crop failure (Bharucha, 2019;Chikwanha et al, 2021), they hold huge potential to bridge yield gaps through natural resource management interventions, since current resource use efficiency is much less than the achievable potential (Anantha et al, 2021a;Wani et al, 2017). Studies indicate that the conversion of degraded pasture lands into productive grasslands is not only helping meet fodder demand but also supporting other ecosystem services (Anantha et al, 2021b;Garg et al, 2021b). A meta-analysis of 86 studies revealed a higher net accumulation of soil carbon, more microbial activity, and other benefits when grasslands are converted into the silvopastoral system (Feliciano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%